Development And Field Test Of Gps-Gsm Drifting Buoy For Measurement Of Sea Surface Current Data - Agung Tri Nugroho; Indra Jaya; Yuli Naulita (Journal of Applied Geospatial Information, 2022)
Spatial data of coastal currents are generally obtained from altimetry satellites. However, the data obtained still has shortcomings, such as the low level of resolution and the need for field validation (ground truth). The electronic drifting buoy (GPS-GSM) is an oceanographic data acquisition instrument that uses a cyber-physical system (SSF) and follows the movement of water around the instrument. The application of the SSF system will facilitate data acquisition from the drifting buoy because the data will be directly entered into the database, transmitted through the GSM system, and monitored in real-time. The design of the ESP32 microcontroller-based instrument is supported by a GPS module for location data acquisition and a GSM module for data transmission to the database. The drifting buoy has dimensions of 52 cm high and 30 cm wide, while the current trap section has dimensions of 26 cm high and 15 cm wide for each wing made of iron. The field test was conducted in the Seribu Islands, DKI Jakarta province, with the current velocity ranged from 0.03 m/s to 0.35 m/s and the average current velocity was 0.19 m/s, while the surface temperature ranged from 26.37 to 27.83 °C with an average value of 26.75 °C.